he problem of physical rehabilitation for breach properties of foot preschool age children. - Kozlov Y.V; Lazareva E.B (Kharkov National Pedagogical University, 2011)
Scientific and methodical literature about preschoolers flat were analyzed in the article. Special means of physical rehabilitation are discussed in. Results of the study of literary sources suggest the need to develop and implement new physical rehabilitation programs in preschools. The greatest effect is expected when based on the foundation of certain numerical showings of biogeometrical sideview of bearing and videotechnology.